Recent Trends in Occupational Segregation by Gender: A Look Across the Atlantic - Juan José Dolado; Florentino Felgueroso; Juan F. Jimeno (Institute for the Study of Labor (IZA), 2002)
In this paper, we analyse the recent patterns of occupational segregation by gender in the EU countries vis-?-vis the US. Given the lack of long time-series data on homogeneous LFS data about occupations and educational attainments for male and female workers in EU countries, we use a single cross section corresponding to 1999 as the basis of comparison, hoping to uncover convergence trends by examining whether the EU-Us differentials in gender occupational segregation decline across age cohorts. The main findings of our study are: (i) gender segregation has been declining across age cohorts in the case of female graduates and has remained steady for those with lower educational levels; in particular, the level of segregation for the former group is higher in the EU than in the US; (ii) gender segregation seems to be positively correlated with the share of part-time jobs; and (iii) there is some evidence, albeit a weak one, that the gender wage gap and occupational segregation are positively correlated, particularly when the Scandinavian countries are excluded from the sample.
Keywords: J16; J71; 330; gender occupational segregation; gender wage gaps; part-time jobs; Arbeitsmarktsegmentierung; Geschlechterdiskriminierung; Lohndifferenzierung; Teilzeitarbeit; EU-Staaten; Vereinigte Staaten